Bank behaviour and resilience : effect of structures, institutions and agents - Bakır, Caner (2013)
This book provides new interdisciplinary and comparative answers as to why banking sectors in 'liberal' and 'coordinated' market economies operated under a shared set of rules during the Global Financial Crisis. Exploring the role of complex interactions among interdependent structures, institutions and agents defines this banking behaviour.
Includes bibliographical references (pages 180-208) and index.
oif 16/06/15, ijb 07/03/2019
Loan
Keywords: Banks and banking; Financial institutions; Monetary policy